On the Adaptation of an AUV into a Dedicated Platform for Close Range Imaging Survey Missions - Yevgeni Gutnik; Aviad Avni; Tali Treibitz; Morel Groper (Journal of Marine Science and Engineering, 2022)
This study presents the redesign of an existing autonomous underwater vehicle (AUV) with limited maneuverability, transforming it into a platform optimized for autonomous, near-seabed visual imaging missions. This work describes the enhancement of the AUV’s maneuverability through the addition of thrusters, the leveraging of a state-of-the-art thrust allocation algorithm, and the development of both a path-following controller and a dedicated imaging system. The performance of the optimized platform is demonstrated in a simulation and in actual real sea visual survey missions.